2016
DOI: 10.1177/0956462415604092
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis infection in African American women who exclusively have sex with women

Abstract: Little is known about whether Chlamydia trachomatis can be sexually transmitted between women or how often it occurs in women who have sex with women (WSW). We investigated Chlamydia trachomatis prevalence and serum Chlamydia trachomatis-specific antibody responses among African American WSW who reported a lifetime history of sex only with women (exclusive WSW) (n = 21) vs. an age-matched group of women reporting sex with women and men (WSWM) (n = 42). Participants completed a survey, underwent a pelvic examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Further, given that women with both male and female lifetime sexual partners and self-identified bisexual women were more likely to receive STI, HIV, and/or HPV tests than women with only male lifetime sexual partners and self-identified heterosexual women, respectively, health care facilities should ensure that the provision of sexual health services is based on unbiased, patient-centered assessments of women’s individual sexual risk and sexual health care needs, as opposed to information on average sexual risk or assumptions (Sexuality Information and Education Council of the United States, 2014). Additionally, our findings suggest that clinical and community-based programs are needed to promote access to and utilization of recommended sexual health services among women with only female lifetime sexual partners and self-identified lesbians, who are underserved despite their risk of acquiring STIs and developing cervical cancer (Kwakwa and Ghobrial, 2003; Muzny et al, 2015; Gorgos and Marrazzo, 2011; Campos-Outcalt and Hurwitz, 2002; Diamant et al, 2000a; Singh and Marrazzo, 2009), as well as regular Pap testing among self-identified bisexual women. Lastly, educational programs that raise awareness about the risk of female-to female STI transmission and cervical cancer among SMW are needed for both women and providers, as are tailored initiatives that connect diverse subgroups of SMW to competent, patient-centered, and affirming sexual health care (Bauer and Welles, 2001; McNair, 2003a, 2003b).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Further, given that women with both male and female lifetime sexual partners and self-identified bisexual women were more likely to receive STI, HIV, and/or HPV tests than women with only male lifetime sexual partners and self-identified heterosexual women, respectively, health care facilities should ensure that the provision of sexual health services is based on unbiased, patient-centered assessments of women’s individual sexual risk and sexual health care needs, as opposed to information on average sexual risk or assumptions (Sexuality Information and Education Council of the United States, 2014). Additionally, our findings suggest that clinical and community-based programs are needed to promote access to and utilization of recommended sexual health services among women with only female lifetime sexual partners and self-identified lesbians, who are underserved despite their risk of acquiring STIs and developing cervical cancer (Kwakwa and Ghobrial, 2003; Muzny et al, 2015; Gorgos and Marrazzo, 2011; Campos-Outcalt and Hurwitz, 2002; Diamant et al, 2000a; Singh and Marrazzo, 2009), as well as regular Pap testing among self-identified bisexual women. Lastly, educational programs that raise awareness about the risk of female-to female STI transmission and cervical cancer among SMW are needed for both women and providers, as are tailored initiatives that connect diverse subgroups of SMW to competent, patient-centered, and affirming sexual health care (Bauer and Welles, 2001; McNair, 2003a, 2003b).…”
Section: Discussionmentioning
confidence: 89%
“…Sexual minority women (i.e., women who self-identify as lesbian, bisexual, or queer and/or have same-sex sexual partners or attractions; SMW) are at risk of acquiring STIs and HIV from sexual contact (e.g., penile-vaginal, penile-anal, vaginal-vaginal, oral-vaginal, vaginal-sex toy) with partners of any sex or gender (Diamant et al, 1999; Xu et al, 2010; Kwakwa and Ghobrial, 2003; Muzny et al, 2011, 2015; Gorgos and Marrazzo, 2011; Marrazzo et al, 2000; Campos-Outcalt and Hurwitz, 2002; Diamant et al, 2000a; Singh and Marrazzo, 2009; Bauer and Welles, 2001). For example, studies show that the prevalence of chlamydia was 7.1% among women with only female and both female and male past-year sexual partners, and the prevalence of herpes simplex virus 2 and HPV was 36.2% and 13%, respectively, among women with only female and both female and male lifetime female sexual partners (Gorgos and Marrazzo, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the rate of transmission of C. trachomatis or N. gonorrhoeae between women is unknown, infection also might be acquired from past or current male partners. Data indicate that C. trachomatis infection among WSW can occur ( 275 , 286 , 308 , 309 ). Data are limited regarding gonorrhea rates among WSW and WSWM ( 170 ).…”
Section: Sti Detection Among Special Populationsmentioning
confidence: 99%
“…In their analysis, enacted sexual stigma (having experienced actual acts of violence and discrimination) increased the odds of STI by 6.5 times, while perceived sexual stigma (being aware of negative social attitudes towards sexual orientation) increased this odd by 2.09 times. In terms of sexual violence, Logie et al 28 found a history of forced sex in 41.7% of their sample, Sandford et al 30 observed this proportion as being 31.1% of Southern African WSW (14.9% by men only, 6.6% by women only, and 9.6% by both women and men), while 5 out of 21 African American exclusive WSW enrolled in the study of Muzny et al 45 had a lifetime history of sexual assault. In Sandford et al 30 , age and having experienced forced sex were the only factors independently associated with a HIV positive serostatus among several variables examined, such as injectable drug use, number of female and male partners, and transactional sex.…”
Section: Genitourinary Sexual Health Ormentioning
confidence: 95%